Analisis Pengaruh Fleksibilitas Kerja dan Kepemimpinan Transformasional terhadap Kinerja Adaptif Melalui Kepuasan Kerja sebagai Variabel Intervening - Putra, Alfian Perdana; Satoto, Eko Budi; Sanosra, Abadi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study intends to investigate the impact of Work Flexibility and Transformational Leadership on Adaptive Performance, with Job Satisfaction serving as an intervening variable. The study focuses on employees at the Secretariat of the Bondowoso Regency DPRD. The survey included 80 personnel from the Bondowoso Regency DPRD Secretariat. This study utilises a Nonprobability Sampling approach known as saturated sample. Researchers utilised questionnaires as a method to get data from participants in this study. The analysis method employed is the Structural Equation Model (SEM) utilising WarpPLS 8.0. The data analysis results indicate that Work Flexibility positively and significantly impacts Adaptive Performance. Transformational Leadership positively and significantly impacts Adaptive Performance. Work flexibility positively and significantly impacts job satisfaction. Job satisfaction positively and significantly impacts adaptive performance. Work flexibility has a favourable but statistically insignificant impact on adaptive performance, mediated by job satisfaction. Transformational Leadership positively and significantly influences Adaptive Performance through Job Satisfaction as an intervening variable. Keywords: Adaptive Performance, Job Flexibility, Job Satisfaction, Transformational Leadership